Desenvolvimento de método multirresíduo para determinação de agrotóxicos em suco de uva integral utilizando método QuEChERS acetato e LC-MS/MS - Albarnaz, Karolaine da Silva (2021)
In the last century, pesticides have been widely used in agriculture due to the many benefits related to the quality and quantity of crops produced. Although they contribute to pest control and increased productivity, the indiscriminate use of pesticides is harmful to human health and the environment. Thus, it became necessary to determine a maximum amount of product that can be present in food, called Maximum Limits and Residues - MRLs. Viticulture is extremely important in Brazilian agriculture as it produces about 1.5 million tons of grapes per year and a large part of the cultivation takes place in the southern region of the country. Half of the grapes produced are sent to processing where by-products are obtained, such as wine and grape juice. Grape juice, because it is easy to prepare and has a high nutritional value, is a drink widely consumed by Brazilians. The quality of grape juice depends directly on the quality of the fruits used in its production, which depends on the use of pesticides. The use of multiresidue methods that are capable of determining different classes and compounds in a single analytical procedure is the best way to carry out the monitoring of pesticide residues in different matrices. Based on this, this work aimed to determine pesticide residues in grape juice through the optimization of the QuEChERS method and analysis by liquid chromatography with tandem mass spectrometry (LC-MS/MS). The parameters that influence the extraction efficiency were studied and, after finding the best extraction conditions, the method was validated. The analysis by LC-MS/MS allowed the determination of the analytes with high selectivity and detectability. The QuEChERS modified acetate method was validated for 153 compounds and the limit of quantification of the method (LOQ) varied from 5 to 10 μg L-1. The validated method was used for the determination of pesticides in grape juice samples. In 17 samples, pesticide residues of different classes and characteristics were found in concentrations ranging from concentrations lower than the LOQ to 41.98 μg L-1. Considering the results obtained, the use of the modified QuEChERS acetate method together with the use of LC-MS/MS proved to be efficient in multi-residue determination of pesticides in grape juice.